Infancy the development of the whole child - Oakes, Lisa M.; Casasola, Marianella; Lobue, Vanessa (SAGE Publications, Inc, 2024)
"This book reflects how we think about and teach infant development. For all three of us, our teaching and research about infancy were shaped by our experiences as mothers of infants. We have learned so much about what infancy really looks like by watching our children grow and change, and we bring this to our teaching. One of our primary aims in writing this book was to provide students and instructors with an engaging textbook to explore the science of the study of infant development. As we embarked on this journey, we had three broad goals. First and foremost, we wanted the book to be interesting, engaging, and enjoyable to read. Our approach was to tell stories-stories about our own children, stories about development, and stories about research. When we teach the topics covered in this book, our lectures are sprinkled with examples from our own children's infancies-it's how we bring the topic to life for our students. So we thought what better way to bring a textbook to life than to include those same stories. We also adopted a more casual writing style than is often found in textbooks. Telling stories about our infants provided a good foundation for this approach, and we have attempted to describe scientific concepts and research details in an approachable, engaging way as well. The feedback we got from undergraduate students who saw early drafts of some of the chapters suggested that we were successful. Not only did they fall in love with our six infants, but they also enjoyed reading the other parts of the text"--